The Effect of the Global Stock Index On the Joint Stock Price Index (JCI) In The Indonesia Stock Exchange, 2015 – 2019 - Sri Budiwati Wahyu Suprapti; Luthfi Hafizh (Publikasi Indonesia, 2022)
The purpose of this study is to identify and analyze the impact of the global index, are the Dow Jones Index (DJIA), Nikkei 225(N225), Shanghai Composite Ind?x Composite (SSEC) and Singapore Straits Times (STI) Against the Jakarta Composite Index (JKSE) on the Indonesia Stock Exchange (IDX). This type of research is explanatory research with quantitative research. This study takes all the time series data listed on the Dow Jones Index, Nikkei 225 Index, Shanghai Stock Composite ?nd?x, Singapore Straits Times Index, and the Jakarta Composite Index (JKSE) for the period January 2015 to December 2019. The research sample used was 60 samples. The data analysis technique used is multiple linear regression analysis. Hypothesis testing results show the Dow Jones Index, Nikkei 225 Index, Shanghai Composite ?xchange Composite ?nd?x, Singapore Straits Times Index, Financial Times Stock Exchange 100 and the Kuala Lumpur Composite Index associated simultaneously with the Jakarta Composite Index (JKSE). The Dow Jones Index has a significant effect on the positive direction of the Jakarta Composite Index (JKSE), The Nikkei 225 index has a significant effect on the negative direction of the Jakarta Composite Index (JKSE), Kuala Lumpur Composite Index 100 has a significant on the positive direction of the Jakarta Composite Index. Shanghai Stock Index Composite Index Singapore Strait Times Index and Financial Times Stock Exchange have no effect on the Jakarta Composite Index (JKSE).